O discurso da sustentabilidade ambiental na produção das biopolíticas atuais: gestão da vida nos tempos da sustentabilidade - Garcia, Margarete Schimidt Mendes (2013)
During its historical course, human society confronted itself with the specificities and vicissitudes of regimes, being the man himself and in each period of time, product and producer, creator and creature of power strategies in the conduct and govern of himself and others. The father, the sovereign and the State have embodied power and all of them, through its own strategies and technologies, acted upon life to optimize it or even take it. Technologies of power renew through time and go from material to immaterial, falling upon minds rather than bodies. In disciplinary society, they've acted to make more docile, useful and increase bodily skills, serving to the purposes of capitalism and the perpetuation of industrial productive systems. Our contemporary society is no longer disciplinary and, because of that, is no longer distinguished by the signs and weights of former times' institutions of disciplinary confinement and their peculiar strategies. The present scenery, set up on a strong appeal towards environmental sustainability, has produced biopower and biopolitics supported by speeches and the adoption of this controversial concept of sustainability to create apparatus and strategies that ultimately conduct to the government of life, of the self and the another. Out of that, results the discontent of the sustainability times, the precification of life and categorized subjects, the conscious consumer and the stakeholder, considered crossing points of truth and power. As a general goal of our research, we investigated the engendering processes of current biopolitics from discourses of environmental sustainability, contributing to the knowledge regarding the performance of these biopolitics and their effects over life management. Methodology was focused on the analysis of production conditions to the discourse of environmental sustainability based on the selected corpus. Theoretical references are fundamentally supported by Michel Foucault, though other authors are called upon to compose theoretical arguments. The research's corpus concentrated on media production, with newspapers, magazines, national and international prints, govern publications, UN and other institutions publications, companies' sustainability reports and communication actions broadcasted through the internet and printed media. Our thesis concludes that the discourse of environmental sustainability creates collective and individual behavioral patterns that, on the one hand, regulate and conduct present life and, on the other, govern by anticipation the future life, promoting the future's administration in the present